(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article provides a comparative analysis of the reflection of folk art, national customs, and myths in Uzbek and American literature through Mark Twain’s “The Adventures of Tom Sawyer” and G‘afur G‘ulom’s “Shum Bola.” In both works, the heroes’ pursuit of freedom, defiance of societal norms, and the influence of beliefs shaped by folk traditions are evident. The article analyzes the role of folk myths, childhood traditions, folklore examples, and national songs in the works, highlighting their literary and aesthetic significance. The research results show that both works, while reflecting the cultural heritage of their respective nations, affirm the important role of folklore in children’s literature.